Analisis Peran Bahasa Asing dalam Profesi Pemandu Wisata di Era Globalisasi - Hafid, Fauziah Sri Andria; Alvira, Idea; Yuliza, Fresti (Journal of Tourism Sciences, Technology and Industry, 2025)
This study explores the significance of foreign language proficiency in enhancing the professionalism of tour guides in the era of globalization. Mastery of foreign languages—particularly English—is a fundamental skill required to establish effective communication with international tourists, improve service quality, and enhance the competitiveness of tourism destinations. This research adopts a qualitative descriptive approach through literature review based on relevant academic sources. The findings indicate that language proficiency not only facilitates interaction but also plays a vital role in shaping tourists’ positive perceptions of destinations and enriching their overall experience. Nevertheless, several challenges remain, including limited access to continuous training, regional disparities in human resource development, and insufficient intercultural communication skills. Consequently, structured and collaborative strategies are necessary—particularly those involving government, educational institutions, and tourism stakeholders—to develop foreign language competencies. Integrating cultural understanding and digital technology into training is recommended as a solution to the challenges posed by globalization in the tourism sector.